Development and Validation of a Communication Skills Training Package Based on Phubbing - Kosari Esfahani, Leila; Jafar Tabatabaei, Toktam Sadat; Jafar Tabatabaei, Samaneh Sadat; jarrahi Freez, Jalil (KMAN Counseling & Psychology Nexus, 2025)
The aim of this research was to develop and validate a communication skills training package based on phubbing. The identified research community consisted of 50 books and articles related to communication skills and phubbing, sourced from reputable domestic and international scientific websites. According to the inclusion criteria, 15 articles and books related to the research variables were selected as the research sample. To identify the training modules, a three-phase coding method by Strauss and Corbin (1998) was used. The proposed training package was designed in 8 sessions with the following topics: "Definition of Phubbing and its Impact on Interpersonal Relationships, Eye Contact Training in Interactions, Verbal Communication, Non-verbal Communication, Empathy and Mutual Understanding Training, Communication Boundaries, Coping Strategies, Practice and Feedback." The content and face validity of the proposed training package was evaluated by 9 experts from the University of Azad, Birjand, using the Lawshe method, resulting in values of 0.78 and 0.89, respectively. The reliability of the proposed training package was examined with two independent coders and found to be 86%. Based on these findings, the package demonstrated adequate validity and reliability.